2016
DOI: 10.1017/s0016756816000832
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian–Ordovician conodonts from slump deposits of the Argentine Precordillera: new insights into its passive margin development

Abstract: The Los Sombreros Formation represents the western continental margin slope deposits of the Argentine Precordillera, a sub-terrane accreted to Gondwana as part of the Cuyania Terrane in early Palaeozoic times. The age of these gravity-driven deposits is controversial and, therefore, a precise biostratigraphic scheme is essential to reveal the evolution of the continental margin. New conodont samplings along with sedimentological and structural analysis carried out in the Los Sombreros Formation in the La Inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Considering the complex structure of the Los Sombreros Formation and the scarcity of biostratigraphic data, the age of the olistostromal unit is controversial, having been attributed to the Ordovician (e.g. Benedetto & Vaccari, 1992;Banchig & Bordonaro, 1994;Keller, 1999;Voldman et al 2009;Voldman et al 2016) or Devonian systems (e.g. Peralta, 2005;Peralta & Heredia, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the complex structure of the Los Sombreros Formation and the scarcity of biostratigraphic data, the age of the olistostromal unit is controversial, having been attributed to the Ordovician (e.g. Benedetto & Vaccari, 1992;Banchig & Bordonaro, 1994;Keller, 1999;Voldman et al 2009;Voldman et al 2016) or Devonian systems (e.g. Peralta, 2005;Peralta & Heredia, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was based on a single sample without accurate stratigraphic location. Recently, Voldman et al (2016) reported species of the genus Cordylodus from the basal part of the Los Sombreros Formation cropping out in the eastern flank of the La Invernada Range. At regional scale, the C. proavus zone was identified in Gondwanan basins of NW Argentina, namely, in the Lampazar (Cajas Range of the Cordillera Oriental of Jujuy (Rao, 1999; later revised by Albanesi et al 2015)), El Moreno (Moya et al 2003) and Alfacito (Zeballo et al 2008) localities of the Cordillera Oriental, and in the Volcancito Formation of the Famatina Range, La Rioja Province (Albanesi et al 2005).…”
Section: B Stratigraphic Correlationmentioning
confidence: 99%
See 3 more Smart Citations